2002
DOI: 10.1038/ng814
|View full text |Cite
|
Sign up to set email alerts
|

Angptl3 regulates lipid metabolism in mice

Abstract: The KK obese mouse is moderately obese and has abnormally high levels of plasma insulin (hyperinsulinemia), glucose (hyperglycemia) and lipids (hyperlipidemia). In one strain (KK/San), we observed abnormally low plasma lipid levels (hypolipidemia). This mutant phenotype is inherited recessively as a mendelian trait. Here we report the mapping of the hypolipidemia (hypl) locus to the middle of chromosome 4 and positional cloning of the autosomal recessive mutation responsible for the hypolipidemia. The hypl loc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
339
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 375 publications
(346 citation statements)
references
References 35 publications
5
339
0
Order By: Relevance
“…Inactivation of either gene in mice results in hypotriglyceridemia (5,32), and both genes elevate plasma TAG levels when expressed at high levels. Humans with complete ANGPTL3 deficiency have very low plasma levels of LDL-C, HDL-C, and TAG (4).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Inactivation of either gene in mice results in hypotriglyceridemia (5,32), and both genes elevate plasma TAG levels when expressed at high levels. Humans with complete ANGPTL3 deficiency have very low plasma levels of LDL-C, HDL-C, and TAG (4).…”
Section: Discussionmentioning
confidence: 99%
“…Genetic studies have revealed that two closely related family members, ANGPTL3 and ANGPTL4, play pivotal roles in the trafficking and metabolism of lipids and lipoproteins (4)(5)(6)(7). Mutations that disrupt ANGPTL3 are associated with greatly reduced plasma levels of triacylglycerol (TAG) and cholesterol in mice (5) and in humans (4). Mice lacking ANGPTL4 also have markedly reduced levels of plasma TAG and cholesterol (8,9), and sequence variations in ANGPTL4 are associated with lower plasma TAG levels in humans (7).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…The ANGPTL3 protein is synthesized by the liver and secreted into the bloodstream 11 . It inhibits lipoprotein lipase 12 , thus delaying clearance of TRLs from the blood and increasing TRL blood concentrations ( Fig.…”
Section: S E K a R K At H I R E S A Nmentioning
confidence: 99%